Social Work in the Time of a Pandemic: COVID-19 and the Need for Resilience-Critical Thinking - Pfaffenstaller, Anna; Zannou, Jacques Love Babatoundé (Springer International Publishing, 2022)
The early effects of COVID-19 are already showing an increase of social inequality and social injustice. If we assume that the social being of humankind is inherent in social work, it should continue to work despite the shock and fundamental changes brought about by COVID-19. Our aim in this chapter is to outline the importance of working with critical assumptions and practices in social work, especially in crisis situations. We base our findings on critical resilience, critical theory, and post-modernism. Our chapter is grounded in the incidents of social work during COVID-19, both in the Global South and Global North. We critically analyze the implementation of social work from the top during the COVID-19 pandemic and the resulting difficulties for social workers and the clients. We conclude that social work needs to be carried out continuously, even in times of crisis. To achieve social transformation, we call for social work that is visibly connected internationally in solidarity and is implemented at the local level.
Created from Fastlane, Scopus look-up
Keywords: COVID-19; Crisis; Critical resilience; Critical theory; Postmodernism; Resilience-critical; Social work; Solidarity